Enhanced Dendritic Cell–based Immunotherapy Using Low-dose Cyclophosphamide and CD25-targeted Antibody for Transplanted Lewis Lung Carcinoma Cells. Issue 3 (April 2015) - Son, Cheol-Hun; Bae, Jae-Ho; Lee, Hong-Rae; Shin, Dong-Yeok; Yang, Kwangmo; Park, You-Soo
Abstract : Regulatory T cells (Tregs) is one of the main obstacles to the success of cancer immunotherapy. The effect of dendritic cell (DC)-based immunotherapy can be attenuated by immune suppressive functions of Tregs. We used a CD25-targeted antibody and low-dose cyclophosphamide (CTX) as immunomodulators to increase the antitumor effect of intratumoral injection of immature DCs into the irradiated tumor cells (IR/iDC). CTX or CD25-targeted antibody alone showed a significant reduction in the number of Tregs within the tumor microenvironment. When they are combined with IR/iDC, the number of Tregs was further reduced. Although IR/IDC showed strong antitumor effects such as reduction in tumor growth, increase in Th1 immune response, and improvement of survival, the therapeutic effect was further improved by combining treatments with immunomodulators. CTX and CD25-targeted antibody showed no significant difference in tumor growth when combined with IR/iDC, but CTX further increased the number of interferon (IFN)-γ-secreting T cells, cytotoxicity, and survival rate. Although irradiation induced depletion of T lymphocytes, administration of DCs recovered this depletion. Particularly, the lymphocytes were more significantly increased when CTX and IR/iDC were combined. Low-dose CTX has already been used as an immunomodulator in clinical trials, and it offers several advantages, including convenience, low-cost, and familiarity to clinicians. However, CD25-targeted antibody cannot only deplete Tregs, but also may affect IL-2–dependent effector T lymphocytes. Therefore, CTX is an effective means to inhibit Tregs, and an effective immunomodulatory agent for multimodality therapy such as combination treatment of conventional cancer therapy and immunotherapy.